2020
DOI: 10.1371/journal.pone.0231896
|View full text |Cite
|
Sign up to set email alerts
|

The novel multi-cytokine inhibitor TO-207 specifically inhibits pro-inflammatory cytokine secretion in monocytes without affecting the killing ability of CAR T cells

Abstract: Cancer immunotherapy using chimeric antigen receptor-armed T (CAR T) cells have been shown to improve outcomes significantly in patients with hematological malignancies. However, cytokine release syndrome (CRS) remains a risk. CRS is characterized by the excessive activation of CAR T cells and macrophages. Signs and symptoms of CRS are usually resolved after steroid administration, but steroids abrogate the expansion and persistence of CAR T cell populations. Tocilizumab is a humanized monoclonal antibody (mAb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 36 publications
(61 reference statements)
0
18
0
Order By: Relevance
“…ANA was used intravenously at the dose of 400 mg/die for 14 days or until the patient was weaned from mechanical ventilation or adverse events related to therapy occurred. The TOCI and ANA schedules were based on dosages indicated for the treatment of cytokine release syndrome [ 18 ] and macrophage activated syndrome [ 19 , 20 ]. The standard supportive management in ICU did not change during the study period.…”
Section: Methodsmentioning
confidence: 99%
“…ANA was used intravenously at the dose of 400 mg/die for 14 days or until the patient was weaned from mechanical ventilation or adverse events related to therapy occurred. The TOCI and ANA schedules were based on dosages indicated for the treatment of cytokine release syndrome [ 18 ] and macrophage activated syndrome [ 19 , 20 ]. The standard supportive management in ICU did not change during the study period.…”
Section: Methodsmentioning
confidence: 99%
“…Modulation of post-transcriptional processes have been also studied as a potential strategy to reduce inflammatory cytokines during CAR-T cell therapy. JTE-607 (TO-207) is a CPSF3 inhibitor that blocks pre-mRNA processing into mature mRNA and has been shown to reduce the processing and secretion of cytokines from monocytes in vitro (82). This mRNA-processing inhibitor had minimal effects on the release of soluble factors from CAR-T cells, suggesting that it selectively inhibits cytokine production in monocytes (82).…”
Section: Current Strategies To Prevent Inflammatory Toxicities During Car-t Cell Therapymentioning
confidence: 99%
“…JTE-607 (TO-207) is a CPSF3 inhibitor that blocks pre-mRNA processing into mature mRNA and has been shown to reduce the processing and secretion of cytokines from monocytes in vitro (82). This mRNA-processing inhibitor had minimal effects on the release of soluble factors from CAR-T cells, suggesting that it selectively inhibits cytokine production in monocytes (82). An early clinical study found that a single dose of JTE-607 appeared to be welltolerated and reduced the severity of endotoxin-induced inflammation in healthy individuals (83).…”
Section: Current Strategies To Prevent Inflammatory Toxicities During Car-t Cell Therapymentioning
confidence: 99%
“…In the case of the folate receptor, we can eliminate folate receptor-overexpressing cancer cells with folic acid linked to fluorescein isothiocyanate (FITC) and anti-FITC CAR T cells [241,242]. TO-207, an mRNA 3 -end processing antagonist, blocks the side-effects of CAR T cells by inhibiting pro-inflammatory cytokine production in monocytes [243]. Dasatinib, a multi-kinase targeted inhibitor, was introduced as an efficient agent to control CAR T-cell activity [244,245].…”
Section: Safety System To Block the Side Effects Of Car T Cellsmentioning
confidence: 99%